The rabies virus research in the inter-scapular glands (brown-fat) of naturally infected bats - Silva, Renato Augusto da; Souza, Ary Moreira de (Pesquisa Agropecuaria Brasileira, 2014)
Among 48 hematophagous bats Desmodus rotundus, rabies virus was isolated from the inter-scapular gland emulsions (brown-fat) of five of these bats (10,4%) by intracerebral mice inoculation. The brain emulsions of two of these bats also gave positive results. The virus strains isolated were determined by the appearance of Negri bodies in the cytoplasm of the nerve cells by microscopic examination of the inoculated brains of mice. The neutralization test employed with one of these strains presented a high titer of neutralization. During the experimentation other species of bats (Carollia sp., Phyllostomus hastatus, Molossus rufus rufus, Molossus temminckii and Diphylla ecaudata) were studied and revealed negative results.